JURIDICIAL ANALYSIS OF LAW ENFORCEMENT BY THE ATTORNEY GENERAL IN REPUBLIC OF INDONESIA ON THE CORRUPTION CASE OF JIWASRAYA INSURANCE BASED ON LAW NUMBER 40 ON 2014 ABOUT INSURANCE - Maulana Agus Salim (Universitas Muhammadiyah Tangerang, 2022)
The problem in this research is Law Enforcement by the Prosecutor's Office of the PT. Insurance Jiwasraya (Persero) which harms customers in terms of criminal law and the issuance of Law Number 40 of 2014 concerning Insurance Jo. Financial Fervices Authority Regulation Number 23/POJK.05/2015 concerning Insurance Products and Insurance Product Marketing is to find out the consequences of law enforcement in the Limited liability company Insurance Jiwasraya (Persero) which is detrimental to the Customer in terms of Criminal Law based on Law Number 40 of 2014 concerning Insurance. The process of collecting and presenting this research is used a normative juridical approach which is research conducted by examining library materials or secondary data. Based on the results of the study, the conclusion in this study is to determine the consequences of law enforcement in the case of Limited liability company Insurance Jiwasraya that harms Customers in terms of Criminal Law based on Law Number 40 of 2014 concerning Insurance begins with conducting an investigation, then prosecution and implementing a decision, the fundamental problem in implementing this handling is an investigation issue because it will determine the entire subsequent process. The authority of the Prosecutor as an investigator, for the time being, is specifically stated in Article 30 paragraph (1) letter d of Law Number 16 of 2004 concerning the Prosecutor's Office stipulating that the Prosecutor's Office has the task and authority to carry out investigations of certain criminal acts based on the law. The Prosecutor's Office has the duty to search for and collect evidence with which to make clear the corruption that occurred and to find the suspect.Keywords: Investigation; Prosecution; Public Prosecution; Insurance